Regresi Kualitas Tenaga Kerja Indonesia: Tinjauan Keterkaitan antara Persyaratan Penampilan Fisik dan Batasan Usia dalam Seleksi Pekerja - Kadek Apriliani; Ni Nyoman Candra Dita Sari; Ni Nyoman Chindera Rahayu (Jurnal Hukum Saraswati, 2025)
This article discusses the phenomenon of declining workforce quality in Indonesia caused by the implementation of physical appearance standards also referred to as being “good-looking” and age restrictions in the recruitment process. In practice, many companies prioritize non-substantial criteria such as attractive appearance and young age over competence, experience, and work skills. This approach not only creates discrimination against certain groups, such as older productive-age workers and individuals with non-ideal physical conditions,but also contributes to a mismatch between labor market demands and the qualifications of recruited workers. Through qualitative data analysis and literature review, this study highlights the negative impacts of discriminatory recruitment practices on productivity, efficiency, and inclusivity in the Indonesian workforce. The importance of reforming employment policies to be more equitable and competency- based is also emphasized to improve the quality of national human resources